The Salivary Microbiome in Polycystic Ovary Syndrome (PCOS) and Its Association with Disease-Related Parameters: A Pilot Study - Lindheim, Lisa; Bashir, Mina; Münzker, Julia; Trummer, Christian; Zachhuber, Verena; Pieber, Thomas R.; Gorkiewicz, Gregor; Obermayer-Pietsch, Barbara (Frontiers in Microbiology, 2016)
Background: Polycystic ovary syndrome (PCOS) is a common female endocrine condition of unclear etiology characterized by hyperandrogenism, oligo/amenorrhoea, and polycystic ovarian morphology. PCOS is often complicated by infertility, overweight/obesity, insulin resistance, and low-grade inflammation. The gut microbiome is known to contribute to several of these conditions. Recently, an association between stool and saliva microbiome community profiles was shown, making saliva a possible convenient, non-invasive sample type for detecting gut microbiome changes in systemic disease. In this study, we describe the saliva microbiome of PCOS patients and the association of microbiome features with PCOS-related parameters. Methods: 16S rRNA gene amplicon sequencing was performed on saliva samples from 24 PCOS patients and 20 healthy controls. Data processing and microbiome analyses were conducted in mothur and QIIME. All study subjects were characterized regarding reproductive, metabolic, and inflammatory parameters. Results: PCOS patients showed a decrease in bacteria from the phylum Actinobacteria and a borderline significant shift in bacterial community composition in unweighted UniFrac analysis. No differences between patients and controls were found in alpha diversity, weighted UniFrac analysis, or on other taxonomic levels. We found no association of saliva alpha diversity, beta diversity, or taxonomic composition with serum testosterone, oligo/amenorrhoea, overweight, insulin resistance, inflammatory markers, age, or diet. Conclusions: In this pilot study, patients with PCOS showed a reduced salivary relative abundance of Actinobacteria. Reproductive and metabolic components of the syndrome were not associated with saliva microbiome parameters, indicating that the majority of between-subject variation in saliva microbiome profiles remains to be explained.